Compact physical and electrical patch antenna engineered for 5G mobile devices and multiband systems - Al Gburi, Ahmed Jamal Abdullah; Jemaludin, Nazrin Haziq; Abdulhameed, Muhannad Kaml; Rafil Hashim, Sarah; Mohammed, Dunya Zeki; Saeidi, Tale; Gupta, Anupma; Zakaria, Zahriladha; Nurhayati, Nurhayati; Hamdy Elabd, Rania (Electromagnetics Academy, 2025)
This article presents a compact multi-band microstrip patch antenna designed for 5G, Ku, and K-band applications. The antenna operates at 3.5 GHz and 15.6 GHz, supporting 5G communications (3.3-3.6 GHz) and satellite applications (15.6-20 GHz). Fabricated on an FR4 substrate (εr = 4.3, tanδ = 0.025) with dimensions of 13 × 10 × 1.6 mm3 (0.15λo × 0.12λo × 0.02λo), where λo represents the wavelength at the lower frequency of 3.5 GHz, the antenna achieves return losses of -19 dB and -39 dB at the respective frequencies, with peak gains of -2.8 dBi and 3.7 dBi. The design's consistency is validated through a comparative analysis with recent studies. The antenna was placed near the ear and mouth area of a human head phantom model to perform a comprehensive SAR analysis. SAR analysis confirms compliance with safety standards, maintaining SAR levels below 2 W/kg. The proposed design demonstrates promising performance for modern communication systems.